1997
DOI: 10.1083/jcb.139.2.469
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Dynamitin (p50) Subunit of the Dynactin Complex Disrupts Dynein-dependent Maintenance of Membrane Organelle Distribution

Abstract: Dynactin is a multisubunit complex that plays an accessory role in cytoplasmic dynein function. Overexpression in mammalian cells of one dynactin subunit, dynamitin, disrupts the complex, resulting in dissociation of cytoplasmic dynein from prometaphase kinetochores, with consequent perturbation of mitosis (Echeverri, C.J., B.M. Paschal, K.T. Vaughan, and R.B. Vallee. 1996. J. Cell Biol. 132:617–634). Based on these results, dynactin was proposed to play a role in linking cytoplasmic dynein to kinetochores and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
599
4
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 614 publications
(659 citation statements)
references
References 75 publications
49
599
4
3
Order By: Relevance
“…Astral MTs seem indispensable for the reclustering of the organelle in a central location (Shima et al, 1998), but intermediate steps in this process might involve the capture of Golgiattached MTs in the centrosomal area to facilitate the reclustering process. Such a model would require Golgi MTs to exhibit reverse polarity or would be quite complicated in terms of molecular motor regulation, because Golgi reclustering is dynein dependent (Corthésy-Theulaz et al, 1992;Fath et al, 1994, Burkhardt et al, 1997Harada et al, 1998). This would be in a way similar to the behavior of chromosomes during mitosis because they have the possibility to directly nucleate MTs in addition to their capture by centrosomal MTs (Carazo-Salas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astral MTs seem indispensable for the reclustering of the organelle in a central location (Shima et al, 1998), but intermediate steps in this process might involve the capture of Golgiattached MTs in the centrosomal area to facilitate the reclustering process. Such a model would require Golgi MTs to exhibit reverse polarity or would be quite complicated in terms of molecular motor regulation, because Golgi reclustering is dynein dependent (Corthésy-Theulaz et al, 1992;Fath et al, 1994, Burkhardt et al, 1997Harada et al, 1998). This would be in a way similar to the behavior of chromosomes during mitosis because they have the possibility to directly nucleate MTs in addition to their capture by centrosomal MTs (Carazo-Salas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with earlier findings by Feiguin et al (1994), who found that the expression of kinesin antisense oligonucleotide rendered the Golgi apparatus more compact, microinjection of antikinesin antibodies inhibited Golgi dispersion along stable, nocodazole-resistant MTs (Minin, 1997). Conversely, the central localization of the Golgi apparatus involves cytoplasmic dynein (Corthésy-Theulaz et al, 1992;Fath et al, 1994;Burkhardt et al, 1997;Harada et al, 1998). It is also worth noting that, in addition to the kinesin-mediated disruption of the central Golgi complex during MT depolymerization, the dispersion of Golgi elements also relies on the reconstitution of mini Golgi stacks at endoplasmic reticulum (ER) exit sites (Cole et al, 1996;Storrie et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We overexpressed p50 (dynamitin), which is known to prevent dynein/dynactin function through dissociation of the dynactin complex, disruption of dynein binding, and cargo anchoring. Dynamitin was preexpressed for 24 h, which induced a characteristic mini-Golgi phenotype indicative of impaired dynein function (Burkhardt et al, 1997;Harada et al, 1998). DNA encoding rab6-GTP was then injected and cells fixed for analysis after 7 h of expression.…”
Section: Rab6-directed Golgi-to-er Transport Is Dependent On Bicd Andmentioning
confidence: 99%
“…Dynein/dynactin drives membrane transport from the ER to the Golgi complex (Presley et al, 1997) and may facilitate inward flow of material within the endocytic pathway, as suggested by in vitro studies of protein transfer from early to late endosomes (Bomsel et al, 1990;Aniento et al, 1993). However, the contributions of dynein and dynactin to endocytic trafficking in vivo have yet to be determined, because previous dynein antibody microinjection studies (Vaisberg et al, 1993;Burkhardt et al, 1997) and evaluation of dynein knock-out mice (Harada et al, 1998) did not ad-dress endosome function in detail. An in-depth exploration of the effects of dynein/dynactin perturbation on endocytic trafficking and dynamics in living cells is clearly warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The extension of ER tubules, the Golgi-to-ER "recycling" leg of the biosynthetic pathway, and the centrifugal movement of lysosomes are thought to require the activity of a plus end-directed motor such as kinesin or a kinesin-related protein (reviewed by Lane and Allan, 1998). Cytoplasmic dynein, the predominant cytosolic minus end-directed motor, in conjunction with its activator, dynactin (Gill et al, 1991), maintains the Golgi complex, endosomes, and lysosomes in the normal juxtanuclear position (Burkhardt et al, 1997;Harada et al, 1998). Dynein/dynactin drives membrane transport from the ER to the Golgi complex (Presley et al, 1997) and may facilitate inward flow of material within the endocytic pathway, as suggested by in vitro studies of protein transfer from early to late endosomes (Bomsel et al, 1990;Aniento et al, 1993).…”
Section: Introductionmentioning
confidence: 99%